(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article presents an analysis of the views of encyclopedic scholars of the East on the spiritual and moral development of the individual. At the same time, the issues of morality, ethics, intellectual maturity, and its harmony with humanity in the development of personality are indicated by Eastern scholars. In particular, the rules of behavior in people, examples, and the relationship between good and evil are highlighted.